Physical and oxidative stability of food emulsions prepared with pea protein fractions. (July 2021) - Hinderink, Emma B.A.; Schröder, Anja; Sagis, Leonard; Schroën, Karin; Berton-Carabin, Claire C.
Abstract: There is a growing interest in replacing dairy proteins with their plant-based counterparts in food emulsions. Plant proteins generally contain a substantial insoluble protein fraction, of which the properties may differ from the soluble proteins. Therefore, the use of a commercial pea protein isolate, its insoluble fraction and whey protein isolate to stabilize oil-in-water (O/W) emulsions is explored. In 100 g/kg O/W emulsions, the use of full pea protein isolate led to physically instable emulsions that showed droplet flocculation and coalescence, whereas its insoluble fraction and whey protein formed physically stable emulsions. The insoluble pea protein fraction was also able to physically stabilize high internal phase O/W emulsions (HIPEs) containing 700 g/kg oil, giving ~10 times higher viscosity than whey protein-based HIPEs. Under oxidative conditions, whey protein-stabilized emulsions showed extensive coalescence, and fast formation of lipid oxidation products. Insoluble pea protein-stabilized emulsions, showed fast lipid oxidation, but this did not affect the physical stability. In contrast, full pea proteins-based emulsions were physically instable in oxidative conditions but showed the lowest accumulation of oxidation products. These results suggest that the constituents of commercial pea protein isolate have specific functionalities, which is important knowledge for the design of stable plant protein-based emulsions. Highlights: Insoluble pea proteins can physically stabilize O/W emulsions. Emulsions stabilized with full PPI are physically unstable. Soluble and insoluble pea protein fractions compete for adsorption. Pea protein fractions form viscous high internal phase emulsions.